The long-run relationship between house prices and inflation in South Africa: an ARDL approach - Inglesi-Lotz, Roula; Gupta, Rangan (International Journal of Strategic Property Management, 2013)
This paper investigates whether house prices provide a suitable hedge against inflation in South Africa by analysing the long-run relationship between house prices and the prices of non-housing goods and services. Quarterly data series are collected for the luxury, large middle-segment, medium middle-segment, small middle-segment and the entire middle segment of house prices, as well as, the consumer price index excluding housing costs for the period 1970:Q1–2011:Q1. Based on autoregressive distributed lag (ARDL) models, the empirical results indicate long-run cointegration between the house prices of all the segments and the consumer price index excluding housing costs. Moreover, the long-run elasticity of house prices with respect to prices of non-housing goods and services, i.e., the Fisher coefficient is greater than one for the luxury segment, virtually equal to one for the small middle-segment, and less than one for the large and medium middle-segments, as well as the affordable segments. More importantly though, the estimated Fisher coefficients are not statistically different from unity – a result consistent with the proposed theoretical framework relating housing prices and consumer prices excluding housing expenditure. In general, we infer that house prices in South Africa provide a stable inflation hedge in the long-run.First Publish Online: 27 Jun 2013